Removal of the Load Traffic in Cellular Network and Data Availability to Maintain Load Balancing - Mahto, M; Shrivas, AK (International Journal of Computer Sciences and Engineering, 2025)
In mobile network several user causing data packet from a network one user to different user, unremarkably user send datain any direction. In mobile Ad hoc network user send data request frequentlywithin the network the provision loss and enormousquantity of power. During the paper, we have a tendency to discuss multiple chunk (part of information segment) throughout the information process mistreatment buffer refreshment to boost data accessibility and data accessibility for durablewithin the network. Ad hoc network is a server consumerprimarily depend network, host user acts as server to satisfydifferent user request. each mobile user to carry temporary storage information chunk and request send Multi node , at that point initial request is ask for distributed to its (requester) the nearest point, the user initial coordinate demand information section with holed copy of information section, if it's match the request ask are response by the closest user otherwise request resend to mobile server